2013
DOI: 10.1091/mbc.e13-02-0092
|View full text |Cite
|
Sign up to set email alerts
|

WASH is required for lysosomal recycling and efficient autophagic and phagocytic digestion

Abstract: Wiskott-Aldrich syndrome protein and SCAR homologue (WASH) is an important regulator of vesicle trafficking. The authors show that, in Dictyostelium, WASH is required for lysosomal hydrolase recycling and function. WASH is therefore crucial for both autophagic and phagocytic degradation, and cells lacking WASH are unable to either survive starvation or grow on certain bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 66 publications
5
84
1
Order By: Relevance
“…This defect was less pronounced with Klebsiella aerogenes (Fig. 9B), consistent with the milder growth defect previously reported (30). To analyze phagocytosis in more detail, we also investigated the ability of WASH-null cells to engulf fluorescently labeled yeast.…”
Section: Wash Drives Recycling Of Surface Proteins From Early Macropisupporting
confidence: 88%
See 3 more Smart Citations
“…This defect was less pronounced with Klebsiella aerogenes (Fig. 9B), consistent with the milder growth defect previously reported (30). To analyze phagocytosis in more detail, we also investigated the ability of WASH-null cells to engulf fluorescently labeled yeast.…”
Section: Wash Drives Recycling Of Surface Proteins From Early Macropisupporting
confidence: 88%
“…Reduction in the surface levels of proteins such as SibC should affect the ability of cells to bind bacteria (52). Previously, we showed that WASHnull cells grow poorly on bacteria, despite normal axenic growth (27,30). As phagocytosis, but not macropinocytosis, is dependent on plasma membrane receptors, we measured the rate of bacterial uptake in WASH-null cells.…”
Section: Wash Drives Recycling Of Surface Proteins From Early Macropimentioning
confidence: 98%
See 2 more Smart Citations
“…Wild-type Dictyostelium cells (Ax2) were axenically cultivated in HL5c medium (Formedium) at 22°C. The Dictyostelium atg1− cells were described (34) and racH− cells from F. Rivero (University of Hull, Hull, United Kingdom). Dictyostelium mutants atg5−, atg6−, and atg7− were received from dictyBase (www.dictybase.org).…”
Section: Methodsmentioning
confidence: 99%